Sovereign Credit Rating Announcement Effects on Foreign Currency Denominated Bond and Equity Markets in Africa. Issue 1 (2nd January 2019) - Mutize, Misheck; Gossel, Sean J.
ABSTRACT: This study investigates the net effect of sovereign credit rating announcements on long-term foreign currency denominated bonds and stock markets in 19 African countries over the period of 1994 to 2014. Using a combination of Granger Causality tests and Dynamic Conditional Correlation (DCC) models, the results show that there is a positive relationship between Africa's stock and bond markets, and weak positive associations between sovereign credit ratings and bond and stock markets. These results imply that both stocks and bonds react negatively (positive) to sovereign credit downgrade (upgrade) announcements. The study further finds that sovereign rating changes affect bond prices more than stock prices because of the volatility in the magnitude of a sovereign downgrade on the default risk premium and bond yields in African markets.